Abscisic acid and betaine eutectic with high light stability and drought resistance and preparation method of abscisic acid and betaine eutectic
By combining abscissic acid with betaine into co-crystals, the abscisic acid is solved in terms of photostability and drought resistance, and its stability and drought resistance in sunlight have been significantly improved, which has extended its effective use time.
Patent Information
- Application Number
- CN202510033780.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The prior art lacks a co-crystal strategy that can improve the photostability and drought resistance of abscissic acid, which leads to the abscisic acid being easily degraded under strong light and reducing its efficacy.
Abscissors and betaine co-crystals with high light stability and drought resistance were prepared by combining abscissors with betaine as co-crystals and evaporating the mixture solution to crystallize.
The photostability and drought resistance of abscisic acid is significantly improved, and its effectiveness in sunlight is extended, and its application frequency and cost are reduced, while reducing potential environmental impacts.
Smart Images

Figure CN119822953A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of drug co-crystals, and in particular to an abscisic acid and betaine co-crystal with high light stability and drought resistance and a preparation method thereof. Background Art
[0002] Abscisic acid, chemical formula is C 15 H 20 O 4 , relative molecular mass 264.321, chemical name (S)-5-(1-hydroxy-4-oxo-2,6,6-trimethyl-2-cyclohexene-1-yl)-3-methyl-(2Z,4E)-pentadienoic acid, its structural formula is shown below. It is difficult to dissolve in water at room temperature, but easily soluble in methanol, ethanol, acetone, chloroform, ethyl acetate and chloroform.
[0003]
[0004] Abscisic acid is an important plant hormone that is widely present in plants, especially in responding to environmental stress and regulating growth and development. Abscisic acid is a secondary metabolite and belongs to the terpenoid class of compounds. Its chemical structure contains a cyclic and a long-chain fatty acid part, which is mainly synthesized by chloroplasts and other organelles in plants. Its synthesis pathway usually involves metabolic conversion from carotenoids, especially in photosynthesis and in response to drought, the synthesis amount will increase significantly. Abscisic acid plays a key role in plants responding to adversities such as drought and salinity. It can promote stomatal closure, thereby reducing water evaporation; at the same time, it plays an important role in seed development and dormancy, and can inhibit seed germination to ensure germination under suitable environmental conditions; exogenous abscisic acid is often used as an effective plant growth regulator, but it is sensitive to light, with a half-life of only 24 minutes, and it will quickly degrade into other products under strong light, greatly reducing its efficacy. Therefore, a method is needed to improve the stability of abscisic acid. Therefore, it is necessary to invent a new solid form to increase the stability of abscisic acid and enhance its effect. Summary of the invention
[0005] The purpose of the present invention is to provide an abscisic acid and betaine co-crystal with high photostability and drought resistance and a preparation method thereof, so as to overcome the problems in the prior art of lack of application of abscisic acid co-crystal strategy in terms of photostability and drought resistance, and the need to improve photostability.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing abscisic acid and betaine co-crystal with high light stability and drought resistance, comprising the following steps:
[0008] (1) mixing abscisic acid, betaine and an organic solvent to obtain a mixed solution;
[0009] (2) The mixed solution is evaporated and crystallized to obtain the abscisic acid and betaine co-crystal.
[0010] Preferably, the molar ratio of abscisic acid to betaine in step (1) is 4:1 to 20:1.
[0011] Preferably, the molar ratio of abscisic acid to organic solvent in step (1) is 1:1400 to 1:2700.
[0012] Preferably, the organic solvent in step (1) is one or more of methanol, ethanol, acetonitrile, ethyl acetate and acetone.
[0013] Preferably, the mixing temperature in step (1) is 25-30°C.
[0014] Preferably, the temperature of the evaporation crystallization in step (2) is 25 to 30° C., and the time of the evaporation crystallization is 30 to 35 hours.
[0015] Preferably, the crystal habit of the abscisic acid and betaine co-crystal in step (2) is needle-shaped.
[0016] The present invention also provides an abscisic acid and betaine co-crystal obtained by the preparation method of the abscisic acid and betaine co-crystal with high light stability and drought resistance.
[0017] The invention also provides an application of abscisic acid and betaine co-crystal with high light stability and drought resistance in a plant regulator.
[0018] The present invention has the following beneficial effects:
[0019] (1) The present invention uses natural plant alkaloid betaine as a ligand, which has good safety. Compared with synthetic chemicals, natural ligands are generally less toxic to the environment and organisms, reducing potential harm to the ecosystem. Since betaine exists naturally in plants and is commonly used for plant growth and protection, its use as a ligand enhances the biocompatibility of co-crystals and ensures the healthy growth of plants. Betaine can not only enhance the stress resistance of plants, but also has antioxidant and anti-inflammatory properties, which is of great significance in improving the overall health of plants and resisting environmental stress. The natural and harmless ligand betaine provides additional safety and eco-friendly advantages for the synthesis of co-crystals, making it more feasible and sustainable in agricultural applications. This feature further enhances the application prospects of the invention and meets the demand of modern agriculture for environmentally friendly materials.
[0020] (2) The solubility of the co-crystal disclosed in the present invention is significantly higher than that of abscisic acid. This improved solubility not only brings convenience to the packaging, transportation and use of the preparation, but also means that plants can absorb abscisic acid more effectively, thereby quickly exerting its biological activity.
[0021] (3) The co-crystals disclosed in the present invention significantly improve the stability of abscisic acid under ultraviolet light, thereby reducing the photodegradation of abscisic acid. This means that when applied in sunlight, the effectiveness of abscisic acid is maintained and plants can benefit from its regulatory effects for a longer period of time. The improvement in photostability can reduce the frequency of abscisic acid application, thereby reducing costs and labor intensity, while reducing potential impacts on the environment.
[0022] (4) The co-crystals disclosed in the present invention enhance the drought resistance of plants. This enhanced drought resistance may come from the synergistic effect of multiple mechanisms, including stomatal regulation, root development, osmotic pressure regulation, antioxidant capacity enhancement, and gene expression regulation. These mechanisms work together to enable plants to better adapt to drought environments, thereby providing an effective solution for agricultural production in the context of global climate change. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is the X-ray powder diffraction pattern of abscisic acid, betaine and the abscisic acid-betaine co-crystal of Example 1;
[0024] Figure 2 The experimental X-ray powder diffraction pattern of the abscisic acid-betaine co-crystal of Example 1 and the powder diffraction pattern calculated by simulating the co-crystal single crystal data;
[0025] Figure 3 The DSC and TGA analysis diagrams of the abscisic acid-betaine co-crystal of Example 1;
[0026] Figure 4 This is a microscope photo of the abscisic acid-betaine co-crystal of Example 1;
[0027] Figure 5 This is a standard curve of the abscisic acid content in the photostability test of the abscisic acid-betaine co-crystal in Example 1;
[0028] Figure 6 Degradation diagrams of abscisic acid, a physical mixture of abscisic acid-betaine and abscisic acid-betaine co-crystal of Example 1;
[0029] Figure 7 The phenotypic changes of plants treated with abscisic acid, a physical mixture of abscisic acid-betaine and the abscisic acid-betaine co-crystal of Example 1;
[0030] Figure 8This is a graph showing the reduction in fresh weight of aerial parts of plants treated with abscisic acid, a physical mixture of abscisic acid-betaine and the abscisic acid-betaine co-crystal of Example 1;
[0031] Fig. 9 The X-ray powder diffraction patterns of the products of Examples 1 to 3 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0032] The present invention provides a method for preparing abscisic acid and betaine co-crystal with high light stability and drought resistance, comprising the following steps:
[0033] (1) mixing abscisic acid, betaine and an organic solvent to obtain a mixed solution;
[0034] (2) The mixed solution is evaporated and crystallized to obtain the abscisic acid and betaine co-crystal.
[0035] In the present invention, the molar ratio of abscisic acid to betaine in step (1) is preferably 4:1 to 20:1, more preferably 6:1 to 18:1, and more preferably 8:1 to 16:1.
[0036] In the present invention, the molar ratio of abscisic acid to the organic solvent in step (1) is preferably 1:1400 to 1:2700, more preferably 1:1600 to 1:2500, and even more preferably 1:1800 to 1:2300.
[0037] In the present invention, the organic solvent in step (1) is preferably one or more of methanol, ethanol, acetonitrile, ethyl acetate and acetone.
[0038] In the present invention, the mixing temperature in step (1) is preferably 25 to 30°C, more preferably 26 to 29°C, and even more preferably 27 to 28°C.
[0039] In the present invention, in step (1), mixing and stirring are required until the solid powder is dissolved to obtain a mixed solution.
[0040] In the present invention, the mixed solution in step (1) needs to be filtered first, and then transferred to a beaker covered with a perforated sealing film for evaporation and crystallization.
[0041] In the present invention, the pore size of the filter membrane is preferably 0.20 to 0.25 μm, more preferably 0.21 to 0.24 μm, and even more preferably 0.22 to 0.23 μm.
[0042] In the present invention, the temperature of the evaporation crystallization in step (2) is preferably 25 to 30°C, more preferably 26 to 29°C, and even more preferably 27 to 28°C.
[0043] In the present invention, the evaporation crystallization time is preferably 30 to 35 hours, more preferably 31 to 34 hours, and even more preferably 32 to 33 hours.
[0044] In the present invention, the crystal habit of the abscisic acid and betaine co-crystal in step (2) is preferably needle-shaped.
[0045] The present invention also provides an abscisic acid and betaine co-crystal having high light stability and drought resistance and obtained by a method for preparing the abscisic acid and betaine co-crystal.
[0046] The present invention also provides an application of abscisic acid and betaine co-crystal with high light stability and drought resistance in plant regulators
[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0048] Example 1
[0049] Use an electronic balance to accurately weigh 100 mg of abscisic acid and betaine in a molar ratio of 4:1 in a crystallizer, add 15 ml of ethanol and stir at 30°C for 2 hours until the solid powder is completely dissolved, then filter (the pore size of the filter membrane is 0.22 μm), transfer the filtrate to a beaker covered with a perforated sealing film, evaporate and crystallize at 30°C, and obtain good quality abscisic acid-betaine eutectic needle crystals after 30 hours.
[0050] Abscisic acid, betaine and the abscisic acid-betaine co-crystal obtained in this example were detected by X-ray diffractometer. Figure 1 shown.
[0051] Then the experimental X-ray powder diffraction pattern of the abscisic acid-betaine co-crystal obtained in Example was compared with the powder diffraction pattern calculated by simulating the co-crystal single crystal data, as shown in FIG. Figure 2 shown.
[0052] from Figure 1It can be seen that the X-ray powder diffraction pattern of the product obtained in this example is at diffraction angles 2θ=5.82±0.2°, 10.45±0.2°, 11.58±0.2°, 12.66±0.2°, 13.39±0.2°, 14.30±0.2°, 15.04±0.2°, 15.39±0.2°, 16.29±0.2°, 17.42±0.2°, 17.68±0.2°, 19.19±0.2°, 20.10±0.2°, 20.36±0.2°, 22.00±0.2°, 23.30±0.2°, 23.87±0.2°, 24. There are diffraction peaks at .21±0.2°, 24.82±0.2°, 25.47±0.2°, 25.73±0.2°, 27.50±0.2°, 29.01±0.2°; 30.53±0.2°, 33.90±0.2°, among which 2θ=5.82±0.2°, 10.45±0.2°, 11.58±0.2°, 12.66±0.2°, 13.39±0.2°, 14.30±0.2°, 17.42±0.2°, 17.68±0.2°, 19.19±0.2°, 24.82±0.2°, 25.47±0.2° are characteristic peaks. These characteristic peaks are different from those of abscisic acid and betaine, indicating that a cocrystal has been formed.
[0053] from Figure 2 It can be seen from the experimental X-ray powder diffraction pattern of the abscisic acid-betaine co-crystal of Example 1 and the powder diffraction pattern calculated by simulating the co-crystal single crystal data. Figure 1 This shows the accuracy of X-ray powder diffraction experiment.
[0054] The abscisic acid-betaine co-crystal obtained in this example was subjected to thermal analysis using a differential scanning calorimeter (DSC) and a thermogravimetric analyzer (TGA) on a TGA / DSC1 (Mettler-Toledo, Switzerland) under a nitrogen atmosphere. 5 to 10 mg of the sample was placed in a crucible and then heated from 273.15 K to 673.15 K at a rate of 10 K / min in a pure nitrogen atmosphere. The results are shown in FIG. Figure 3 shown.
[0055] from Figure 3 It can be seen that the melting point of the abscisic acid-betaine eutectic obtained in this example is 144.15°C.
[0056] Figure 4 This is the product appearance picture of this embodiment, from Figure 4 It can be seen that the abscisic acid-betaine eutectic product obtained in this example has a white needle-like appearance, and its solubility in water at 25° C. increases by 102.54%.
[0057] The abscisic acid-betaine co-crystal obtained in this example was subjected to a photostability test, and the determination method was as follows: three saturated aqueous solutions of abscisic acid, abscisic acid-betaine co-crystals, and a physical mixture of abscisic acid-betaine were prepared. Each of the three solutions was transferred to a quartz test tube wrapped in aluminum foil and treated in the dark. All test tubes were then exposed to a light source for 22 hours, which consisted of a 300W high-pressure mercury lamp equipped with a 365nm ultraviolet filter. Samples were taken at specified time intervals and centrifuged for 3 minutes. The supernatant was analyzed by HPLC (Agilent 1200, Agilent Technologies, Inc., USA). The standard curve of abscisic acid content is shown in Figure 2. Figure 5 All experiments were repeated three times and the results are shown in Figure 6 shown.
[0058] from Figure 5 and Figure 6 It can be seen that after 2 hours of UV irradiation, the physical mixture of abscisic acid and abscisic acid-betaine both degraded by nearly 60%, while the abscisic acid-betaine cocrystal remained intact with 91.48% remaining. The degradation of the physical mixture of abscisic acid-betaine was similar to that of abscisic acid, indicating that the cocrystals synthesized in the experiment exhibited unique interactions in both solid and liquid forms, which have great advantages over simple physical mixtures. After 22 hours of UV irradiation, the abscisic acid-betaine cocrystal continued to show superior photostability with a residual rate of 92.18%, while the other formulations were mostly degraded.
[0059] The drought resistance of the abscisic acid-betaine co-crystals obtained in this example was evaluated, and the determination method was as follows: the wheat seeds were vernalized and then sown in a growth medium composed of vermiculite and soil in a ratio of 1:1 (V / V), and the seeds were covered with a 1 cm layer of soil. After 2 weeks of normal watering, the control group was watered with 50 ml per day. In contrast, the other groups received different treatments under drought conditions, namely, spraying 10 ml of abscisic acid, abscisic acid-betaine co-crystals, a physical mixture of abscisic acid-betaine, and pure drought treatment every day. All plant treatment groups were maintained under light conditions, and each treatment was repeated three times. After five days, the phenotypic changes of the plants were observed, and the fresh weight reduction (FWR) of the aboveground parts was recorded based on the following equation.
[0060]
[0061] Phenotypic changes in plants such as Figure 7 shown.
[0062] from Figure 7It can be seen that under pure drought conditions, the plants showed obvious wilting, and the leaves turned yellow, curled, and narrowed. Under drought conditions, spraying saturated solutions of abscisic acid and abscisic acid-betaine physical mixture had similar effects on plant growth. It is worth noting that the plants treated with abscisic acid-betaine eutectic maintained the most upright posture, and the phenotypic characteristics were very similar to those of plants under normal water irrigation conditions, indicating that abscisic acid-betaine eutectic has excellent light stability and drought resistance.
[0063] The aboveground fresh weight loss (FWR) was further quantified, as Figure 8 shown.
[0064] from Figure 8 It can be seen that the results are consistent with Figure 7 The phenotypic changes observed in the study were consistent with those observed in the study. Under pure drought conditions, plants reduce the growth of their aboveground parts to minimize water loss due to transpiration, resulting in a significant reduction in leaf area and, therefore, a reduction in fresh weight. Compared with other treatments, the reduction in fresh weight of plants sprayed with abscisic acid-betaine cocrystals (4.45%) was significantly the lowest. This suggests that abscisic acid-betaine cocrystals effectively improve the drought resistance of plants.
[0065] Example 2
[0066] Use an electronic balance to accurately weigh 100 mg of abscisic acid and betaine in a molar ratio of 12:1 in a crystallizer, add 15 ml of ethanol and stir at 30°C for 2 hours until the solid powder is completely dissolved, then filter (the pore size of the filter membrane is 0.22 μm), transfer the filtrate to a beaker covered with a perforated sealing film, evaporate and crystallize at 30°C, and obtain good quality abscisic acid-betaine eutectic needle crystals after 35 hours.
[0067] The abscisic acid-betaine co-crystal obtained in this example was detected by X-ray diffractometer. Fig. 9 shown.
[0068] from Fig. 9It can be seen that the X-ray powder diffraction pattern of the product has a diffraction angle of 2θ = 5.80 ± 0.2°, 10.43 ± 0.2°, 11.56 ± 0.2°, 12.64 ± 0.2°, 13.37 ± 0.2°, 14.31 ± 0.2°, 15.04 ± 0.2°, 15.35 ± 0.2°, 16.27 ± 0.2°, 17.43 ± 0.2°, 17.68 ± 0.2°, 19.17 ± 0.2°, 20.10 ± 0.2°, 20.36 ± 0.2°, 22.01 ± 0.2°, 23.30 ± 0.2°, 23.87 ± 0.2°, 24.21 There are diffraction peaks at 2θ=5.80±0.2°, 10.43±0.2°, 11.56±0.2°, 12.64±0.2°, 13.37±0.2°, 14.31±0.2°, 17.43±0.2°, 17.68±0.2°, 19.17±0.2°, 24.83±0.2°, and 25.49±0.2°. These characteristic peaks are different from those of abscisic acid and betaine, indicating that a cocrystal has been formed.
[0069] DSC results showed that its melting point was 143.68°C, the product had a white needle-like appearance, and its solubility in water at 25°C increased by 100.16%.
[0070] The abscisic acid-betaine eutectic needle crystals obtained in this example were subjected to a light stability test according to the method of Example 1. After 22 hours of ultraviolet irradiation, the abscisic acid-betaine eutectic continued to exhibit excellent light stability with a residual rate of 90.10%, while the other formulations were mostly degraded.
[0071] The drought resistance of the needle-shaped abscisic acid-betaine eutectic crystals obtained in this example was evaluated according to the method of Example 1. The plants treated with abscisic acid-betaine eutectic under drought conditions were still the strongest, and the phenotypic characteristics were very similar to those of the plants under normal irrigation conditions, indicating that the abscisic acid-betaine eutectic had excellent drought resistance. The fresh weight reduction rate (4.98%) of the plants treated with abscisic acid-betaine eutectic was significantly lower than that of the other treatments.
[0072] Example 3
[0073] Use an electronic balance to accurately weigh 100 mg of abscisic acid and betaine in a molar ratio of 20:1 in a crystallizer, add 15 ml of ethanol and stir at 30°C for 2 hours until the solid powder is completely dissolved, then filter (the pore size of the filter membrane is 0.22 μm), transfer the filtrate to a beaker covered with a perforated sealing film, evaporate and crystallize at 30°C, and obtain good quality abscisic acid-betaine eutectic needle crystals after 32 hours.
[0074] The abscisic acid-betaine co-crystal obtained in this example was detected by X-ray diffractometer. Fig. 9 shown.
[0075] from Fig. 9 It can be seen that the X-ray powder diffraction pattern of the product has diffraction angles 2θ=5.84±0.2°, 10.44±0.2°, 11.57±0.2°, 12.65±0.2°, 13.37±0.2°, 14.32±0.2°, 15.07±0.2°, 15.37±0.2°, 16.28±0.2°, 17.45±0.2°, 17.69±0.2°, 19.18±0.2°, 20.11±0.2°, 20.37±0.2°, 22.02±0.2°, 23.30±0.2°, 23.87±0.2°, 24.22±0.2° There are diffraction peaks at 0.2°, 24.85±0.2°, 25.50±0.2°, 25.72±0.2°, 27.51±0.2°, 29.02±0.2°; 30.54±0.2°, 33.92±0.2°, among which 2θ=5.84±0.2°, 10.44±0.2°, 11.57±0.2°, 12.65±0.2°, 13.37±0.2°, 14.32±0.2°, 17.45±0.2°, 17.69±0.2°, 19.18±0.2°, 24.85±0.2°, 25.50±0.2° are characteristic peaks. These characteristic peaks are different from those of abscisic acid and betaine, indicating that a cocrystal has been formed.
[0076] DSC results showed that its melting point was 144.04°C, the product had a white needle-like appearance, and its solubility in water at 25°C increased by 98.67%.
[0077] The abscisic acid-betaine eutectic needle crystals obtained in this example were subjected to a light stability test according to the method of Example 1. After 22 hours of ultraviolet irradiation, the abscisic acid-betaine eutectic continued to exhibit excellent light stability with a residual rate of 91.06%, while the other formulations were mostly degraded.
[0078] The drought resistance of the needle-shaped abscisic acid-betaine eutectic crystals obtained in this example was evaluated according to the method of Example 1. The plants treated with abscisic acid-betaine eutectic under drought conditions were still the strongest, and the phenotypic characteristics were very similar to those of the plants under normal irrigation conditions, indicating that the abscisic acid-betaine eutectic had excellent drought resistance. The fresh weight reduction rate (5.12%) of the plants treated with abscisic acid-betaine eutectic was significantly lower than that of the other treatments.
[0079] Comparative Example
[0080] Use an electronic balance to accurately weigh 100 mg of abscisic acid and betaine in a molar ratio of 1:3 into a crystallizer, add 15 ml of acetone and stir at 30°C for 2 hours until the solid powder is completely dissolved, then filter (the pore size of the filter membrane is 0.22 μm), transfer the filtrate to a beaker covered with a perforated sealing film, evaporate and crystallize at 30°C, and only a single component is obtained after a period of time.
[0081] The X-ray powder diffraction pattern obtained in this comparative example is as follows Fig. 9 shown.
[0082] In summary, the ABA-betaine cocrystal significantly increased the solubility of ABA and showed remarkable stability under light conditions. In addition, this cocrystal effectively improved the drought resistance of plants, verifying its potential as a plant growth regulator. This study provides an effective strategy to improve the effectiveness of ABA as a plant growth regulator, which has positive significance for cost reduction and environmental safety.
[0083] As can be seen from the above embodiments, the present invention provides a method for preparing abscisic acid and betaine co-crystals with high light stability and drought resistance, comprising the following steps: mixing abscisic acid, betaine and an organic solvent to obtain a mixed solution; evaporating and crystallizing the mixed solution to obtain the abscisic acid and betaine co-crystals. The present invention uses natural plant alkaloid betaine as a ligand, which has good safety. Compared with synthetic chemicals, natural ligands are generally less toxic to the environment and organisms, reducing potential harm to the ecosystem. The solubility of the co-crystal disclosed in the present invention is significantly higher than that of abscisic acid. This improved solubility not only facilitates the packaging, transportation and use of the preparation, but also means that plants can absorb abscisic acid more effectively, thereby quickly exerting its biological activity. The co-crystal disclosed in the present invention significantly improves the stability of abscisic acid under ultraviolet light irradiation, thereby reducing the photodegradation of abscisic acid. The co-crystal disclosed in the present invention enhances the drought resistance of plants. This enhanced drought resistance may come from the synergistic effect of multiple mechanisms, including stomatal regulation, root development, osmotic pressure regulation, improved antioxidant capacity and regulation of gene expression.
[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing abscisic acid and betaine co-crystal with high photostability and drought resistance, characterized in that: The following steps are involved: (1) mixing abscisic acid, betaine and an organic solvent to obtain a mixed solution; (2) The mixed solution is evaporated and crystallized to obtain the abscisic acid and betaine co-crystal.
2. The preparation method according to claim 1, characterized in that: In the step (1), the molar ratio of abscisic acid to betaine is 4:1 to 20:
1.
3. The preparation method according to claim 1, characterized in that: The molar ratio of abscisic acid to the organic solvent in the step (1) is 1:1400 to 1:2700.
4. The preparation method according to claim 1, characterized in that: The organic solvent in step (1) is one or more of methanol, ethanol, acetonitrile, ethyl acetate and acetone.
5. The preparation method according to claim 1, characterized in that: The mixing temperature in step (1) is 25-30°C.
6. The preparation method according to claim 1, characterized in that: The temperature of the evaporation crystallization in the step (2) is 25 to 30° C., and the time of the evaporation crystallization is 30 to 35 hours.
7. The preparation method according to claim 1, characterized in that: The crystal habit of the abscisic acid and betaine co-crystal in the step (2) is needle-shaped.
8. Abscisic acid and betaine co-crystal obtained by the method for preparing the abscisic acid and betaine co-crystal with high light stability and drought resistance according to any one of claims 1 to 7.
9. Use of the abscisic acid and betaine co-crystal with high light stability and drought resistance as claimed in claim 8 in plant regulators.
Citation Information
Patent Citations
Screening For Solid Forms By Ultrasound Crystallization And Cocrystallization Using Ultrasound
US20070287194A1